OP0040 Peripheral Blood Transcriptional Changes Elicited by Treatment of Systemic Lupus Erythematosus (SLE) Patients with Dapirolizumab Pegol (A Pegylated Anti-CD40L Fab'). (15th July 2016) - Ranger, A.; Allaire, N.; Colman, P.; Wager, C.; Li, H.; Thai, A.; Cullen, P.; Otoul, C.; Czerkowicz, J.; Roberts, C.; Chamberlain, C.; Burkly, L.; et al.
Abstract : Background: CD40-CD40L is a critical costimulatory pathway necessary for normal immune function (including B cell differentiation, germinal center formation and antibody isotype switching) and strongly implicated in the pathogenesis of autoimmune disorders such as SLE. In a randomised, placebo-controlled, parallel group Phase 1 study, dapirolizumab pegol (DZP), a pegylated anti-CD40L Fab', was administered to patients with active SLE on stable background therapy (NCT01764594 ). Objectives: To examine the effect of DZP on peripheral blood RNA transcripts associated with immune cell subsets and SLE disease activity as biomarkers for proof of biological activity. Methods: Twenty-four subjects were randomised (2:1) to receive DZP or placebo and 22 subjects completed the study. Subjects randomised to DZP received a loading dose of 30 mg/kg followed by 15 mg/kg every 2 weeks for a total of 6 doses and were subsequently followed for 18 weeks. For transcriptional analyses, blood was collected in PAXgene tubes at Weeks 0, 2, 4, 8, 12, 20 and 28. A panel of 96 genes was selected for analysis by qPCR including genes expressed in plasma cells, B cells and other immune cells. Also included were transcripts associated with SLE disease activity, such as the Type I Interferon (IFN) signature. For the analysis, genes were grouped into functional domains (such as B cells, T cells, IFN) and decision criteria were designed to identify consistent expression changes within a domain. At a gene level, a positive signal required a >2 fold up- or down-regulated change from baseline, and occurring on at least 2 successive visits. Differences in changes from baseline between DZP and placebo groups were considered significant at <0.0894 (to achieve a 5% false positive rate at a functional domain level). Results: Changes in genes within the plasma cell and B cell domains had the greatest degree of statistical significance. Among the plasma cell genes, the DZP group exhibited rapid decreases in the expression of several immunoglobulin-associated genes (secretory IgA, IgG, Igk, Igl, J chain) starting at Week 2 and maintained over the treatment period. Among the B cell genes, the DZP group showed a transient increase in CD19 and CD20 RNA transcripts at Week 2 that was mirrored by flow cytometry data. Additionally, there were transient increases in membrane IgD, membrane IgM and TCL1A genes which are associated with naïve B cells. Several of the patients in the DZP group also exhibited a ≥2 fold reduction in the expression of IFN-responsive genes (MX1, OAS1, IFITM3, G1P2) for at least 2 time points. No other consistent changes in other functional group expression patterns were observed. Conclusions: In summary, DZP treatment resulted in changes in peripheral blood RNA transcripts found in plasma cells and B cells consistent with the inhibition of CD40L:CD40 signaling. A trend in the reduction of the IFN signature was also observed with DZP. The utility of this approach to monitor biological activity, early clinical response and patient stratification will be further explored. Disclosure of Interest: A. Ranger: None declared, N. Allaire Employee of: Biogen, P. Colman Employee of: Biogen, C. Wager Employee of: Biogen, H. Li Employee of: Biogen, A. Thai Employee of: Biogen, P. Cullen Employee of: Biogen, C. Otoul Employee of: UCB Pharma, J. Czerkowicz Employee of: Biogen, C. Roberts Employee of: Biogen, C. Chamberlain Shareholder of: UCB Pharma, Employee of: UCB Pharma, L. Burkly Employee of: Biogen, G. Johnston Shareholder of: UCB Pharma, Employee of: UCB Pharma